Influencing factors and paths of direct carbon emissions from the energy consumption of rural residents in central China determined using a questionnaire survey - Ma, Xiao-Wei; Wang, Mei; Lan, Jing-Ke; Li, Chuan-Dong; Zou, Le-Le (Advances in climate change research, 2022)
Rural residents have unique lifestyle characteristics, energy consumption methods, energy-saving behaviors, and awareness. And the direct carbon emission from rural residents is based on the combined effect of multiple factors. In order to address the complexity of factors affecting the direct carbon emissions from rural household, this study used a structural equation model to examine the effect of multi-factor variables on direct carbon emissions from rural households in central China. Data were collected using questionnaires and surveys in six cities in central China to reflect the daily reality of rural residents. The results show that quality of life and awareness of energy conservation can affect the direct carbon emissions of rural residents. Family characteristics and awareness of energy conservation affected carbon emissions indirectly by affecting the daily behaviors and quality of life of the residents; consumption characteristics, energy-saving behaviors, and energy conservation policies are not the main factors contributing to the direct carbon emissions of the residents. Based on the results, future studies can focus on energy conservation education, improvement of the living habits, coal energy use efficiency, and energy consumption structure of residences.